Do cultural differences affect users' e‐learning adoption? A meta‐analysis. (25th July 2020) - Zhao, Yang; Wang, Ning; Li, Yixuan; Zhou, Ruoxin; Li, Shuangshuang
Abstract: The great advantages of e‐learning have been recognized, and efforts have been made to promote e‐learning adoption. Despite valuable research achievements from technology adoption, previous studies built their models from different perspectives. In this study, to offer a comprehensive research model on e‐learning adoption, we integrated these models (ie, TAM, TPB and IDT) and included culture as a moderator. Based on 45 relevant empirical research, this study conducted a meta‐analysis to explore key determinants of users' attitude and behavioral intention to adopt e‐learning. Combined with traditional technology acceptance theories and innovation diffusion theory, we developed a comprehensive model and explored the moderating role of culture. The results indicate that this integrated technology acceptance model can be applied to better understand e‐learning adoption. The moderator analysis shows that the influence of subjective norms and self‐efficacy on users' behavior intention is more salient in the collectivistic culture, whereas perceived usefulness is more important for online learners in an individualistic culture.